Extended analysis of types of stride pattern and pacing strategy in 400 m hurdle run - Iskra, J.; Corluka, M.; Vodicar, J.; Mackala, K. (Acta Kinesiologica, 2021)
The study aims to evaluate the strategy of men`s 400 m hurdles (400 mH) run of the best hurdlers in the world, implementing five types of stride pattern. The analysis included 243 individual runs of 114 leading world hurdlers at a distance of 400 mH, participating in the international championship (39) in1968-2015. Data was obtained from own sources, published literature, and projects implemented by the IAAF (International Association of Athletics Federations) during the major athletics competitions. The parameters analyzed in the study included the temporal parameters and the spatial structure (space parameters) of 400 mH race. The adopted strategy of the 400 mH run determines significant differences in the temporal structure of the first part of the run and the spatial structure in its second part. Additionally, the differences determining the time strategy in the 400 mH run concern the distance from the first to the fifth hurdle. The number of steps is of particular importance in the second part of the distance, mainly between the 6thand 8thhurdles. The stride patterns determine the course of the competition (pacing strategy) in the 400mH run. In 400 mH training, about 30% time should be devoted to technical training, which will strengthen the effective use of "weaker" lead leg (attacking leg).